Perancangan Sistem Informasi Akademik Pesantren Berbasis Web Menggunakan Metode Research and Development - Hidayatullah, Sukma; Rosyidi, Lukman (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
Pesantren Teknologi Informasi dan Komunikasi (PeTIK) is a technology-based educational institution that faces challenges in managing academic data due to its manual system using Google Spreadsheets. This study aims to design and develop a web-based academic information system to enhance efficiency and accuracy in recording grades, attendance, and lecture schedules. The Research and Development (R&D) method with a qualitative approach was employed, involving admins, teachers, and students as research subjects. Data were collected through literature studies, interviews, observations, and documentation, and analyzed descriptively. The system was developed using Node.js and Express.js for the backend, React.js for the frontend, and MySQL as the database. Testing was conducted using black-box methods and user evaluations. The results show that the system improved work efficiency, indicated by reduced time in academic data recording, fewer input errors, and a streamlined academic workflow. The system also enhanced accessibility and transparency of academic information. In conclusion, the academic information system successfully replaced manual processes with integrated, efficient, and user-friendly digital workflows. Further development is recommended to include notification features, report generation, and automated schedule-change management to support more optimal academic operations.